Implikasi Hukum Perdata terkait Utang Piutang yang Sudah Daluwarsa - Nita Ayuningsih; Sylvania Okta Aurelia; Vania Aulia; Alvi Septia Listyani; Ahmad Amir Ruddin (Universitas Wahid Hasyim, 2024)
In reality, borrowing money is one way for people to get the funds they need. Agreements are usually made in writing, orally, or under the hand, in accordance with the demands to be carried out in good faith and legal certainty. However, as the era of lending and borrowing develops, there must be strong evidence to prove that a lending and borrowing event has occurred. Usually, the parties agree on a certain period of time when making an agreement. Furthermore, the obligation is considered to have exceeded the time period in the agreement if the time limit given to complete the task has passed. However, in this case, the creditor only collected the amount from the debtor for 34 years when the agreement expired. What happens if the creditor comes after the debt has passed that time? According to civil law, debts must still be paid even if the debtor has passed away. Therefore, Article 1362 of the Civil Code states that there will be compensation in the event of default